KORELASI ANTARA KONSUMSI PROTEIN, ENERGI DAN BULAN LAKTASI DENGAN PRODUKSI SUSU SAPI PERAH DI KABUPATEN SEMARANG - Anis Muktiani (JURNAL LITBANG PROVINSI JAWA TENGAH, 2017)
The purpose of this study is to evaluated the relationship of energy consumption (total digestible nutrients), intake protein and month of lactation with milk production on dairy cattle in Semarang Regency. The materials used was 40 dairy cattle between 1-9 month of lactation. It were grouped into 3 groups of month lactation including group 1 (1-3 month), group 2 (4-6 month) and group 3 (7-9 month). The measured variables were dry matter consumption, crude protein, and total digestible nutrients as independent variables and milk production as a fixed variable. The effect of independent variables on fixed variables was tested using correlation test and linear regression. The result showed that milk production of each group 1,2 and 3 was 12.12, 9.40, and 7.73 liters / day. The crude protein content and total digestible nutrients ration ranged between 12-13.7% and 62-66%. The consumption of crude protein and total digestible nutrients had no apparent correlation with milk production in dairy cattle in Semarang Regency, but milk production was strongly influenced by lactation (p <0.01). Correlation value (r) between lactation month with milk production showed moderate relationship (r = 0,55) with regression equation Y = 13.258-0,717X, that the milk production will decrease equal to 0,717 liter every month. The conclusion of this study is consumtion of protein and energy is not correlated with dairy milk production in Semarang Regency. Lack of consumption of crude protein and total digestible nutrients in early lactation leads to lower production presistence than normal milk production patterns.